Pengaruh Beban Iklan dan Intensitas Persediaan terhadap Agresivitas Pajak - Anggun Putri Romadhina (Journal of Economics and Management Scienties, 2022)
This study aims to test and provide empirical evidence of the effect of advertising expenses and inventory intensity on tax aggressiveness conducted by Manufacturing companies of the goods and consumption sector listed on the Indonesia Stock Exchange. The sample was selected using the purposive sampling method, with a research year period of 5 years starting from 2013-2017. The results of this study indicate that the advertising expenses has a significant effect on tax aggressiveness. While inventory intensity has not affect the tax aggressiveness of the goods and consumption sector Manufacturing companies listed on the Indonesia Stock Exchange. Advertising load and inventory intensity simultaneously or together affect the tax aggressiveness.